Enzyme-morphological criteria for diagnosing the stages of hepatorenal syndrome development in canine babesiosis - Horalskyi, L. P.; Sokulskyi, I. M.; Kolesnik, N. L.; Gutyj, B. V.; Pavliuchenko, O. V.; Shevchuk, S. Y. (Regulatory Mechanisms in Biosystems, 2026)
The study presents the characterization of the stag es of babesiosis manifestations depending on the sex of dogs, as well as enzymatic diagnostics of liver pathology and the determination of urea and creatinine concentrations in the blood serum of dogs with acute babesiosis. Additionally, we investigated the macro- and microscopic structure of the organs in dogs affected by acute babesiosis . Based on the observational data, specific features of the course of babesiosis in dogs were identified, indicating a stage-by-stage progression of the disease with a sequential transition from the incubation period to the period of clinical manife s tation. According to the anamne sis data, the incubation period ( from pathogen entry into the body to the appearance of the first clinica l signs ) lasted 5–8 days. This duration showed seasonal variation: 6–8 days in spring and 5–6 days in autumn. Clinical signs of acute babesiosis were identified in 45 spontaneously infected dogs of different breeds (German s hepherd, Central Asian s hepherd, and Rottweiler), aged 1.5–8 . 0 years, of both sexes, kept in individual households and some kennels in Zhytomyr. The intensity of Babesia canis invasion was reflected in the severity of clinical signs and depended on the duration of disease progre s sion: T he longer the pathological process persisted, the greater the intensity of invasion, which proportionally increased the seve r ity of the disease. Based on the analysis of the obtained data, three stages of acute babesiosis were identified. Among the total group of spontaneously infected dogs (n = 45), 16 animals were assigned to stage I, 13 to stage II, and 16 to stage III. The degree of hepatic parenchymal damage depended on the nature of the injurious factor, duration of exposure, and individual susceptibi l ity. Histological examination of the liver revealed disorganization of hepatic cords in certain lobular areas, focal hemorrhages, and conge s tion of capillaries. The interlobular connective tissue exhibited serous edema . Interlobular bile ducts were dilated and filled with bile. Most hepatocytes were in a state of granular (protein) dystrophy , with accumulation of brown pigment (hemofuscin) in the cytoplasm. These cells also showed signs of atrophy and severe destructive changes, leading to intrahepatic cholestasis. This was confirmed by a significant increase in the activity of the cholestatic enzyme gamma-glutamyl transpeptidase, which in the dogs at stage III of the disease exceeded normal values fourfold. Histological examination of the kidneys revealed granular dystrophy and necrosis of the epithelial cells of the convoluted renal tubules, as well as hemorrhages in both cortical and medullary regions. These changes led to impaired renal circulation and decreased filtration, excretory, and reabsorptive functions. The results of this study, along with the data from other researchers, allow us to identif y the patterns in morphological changes in the organs and tissues during the acute course of the disease and contribute to the understanding of the functional significance of their structural components.